PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR IPA PESERTA DIDIK SEKOLAH DASAR KELAS V (Adi Widya: Jurnal Pendidikan Dasar, 2024)
The science learning process obtained in elementary school is not just memorizing concepts to produce a complete understanding, but rather the science concepts are studied and understood well so they are not easily forgotten. This research aims to analyze the influence of the guided inquiry learning model on the science learning outcomes of 5th grade elementary school students. This type of research is quantitative research using a quasi experiments design, namely pretest posttest nonequivalent control group design. The research was carried out at SD Negeri 23 Pemecutan, West Denpasar for six (months) starting from the planning. The population of this study was all 5th grade students at SD Negeri 23 Pemecutan, West Denpasar. The sampling technique in this research used non-probability with saturated sampling to obtain an experimental class and a control class. The data collection technique uses multiple choice type test. The test consists of 20 questions that have been tested for content validity, item validity, reliability test, discrimination test, level of difficulty and effectiveness of distractors. Next, the pretest and posttest results were analyzed using inferential statistics assisted by SPSS 25.0 which includes normality tests, homogeneity tests, and hypothesis testing with the t-test. The results of hypothesis testing via the t-test show that sig.2 tailed is 0.000 < 0.05, which means that H0 is rejected and H1 is accepted, so that a conclusion can be drawn, namely that there is a significant influence of the guided inquiry learning model on the 5th grade students science learning outcomes of SD Negeri 23 Pemecutan, West Denpasar.